Radiological characterisation for the clearance of burnable waste produced at CERN. (June 2023) - Harbron, Richard; Charousset, Renaud; Dumont, Gerald; Magistris, Matteo; Menaa, Nabil; Giunio Pisano, Paolo; Theis, Christian
Abstract: Burnable waste produced at CERN during upgrading, maintenance and dismantling campaigns may be contaminated with radioactive nuclides produced through activation of accelerator components. Here, we present a methodology for the radiological characterisation of burnable waste, which takes into account the wide range of potential activation conditions (beam energy, material composition, location, irradiation and waiting time). Waste packages are measured using a total gamma counter, with the sum of clearance limit fractions estimated using the fingerprint method. Gamma spectroscopy was found to be unsuitable for classifying this waste due to the long counting times required to identify many expected nuclides, but was retained for quality control purposes. Using this methodology, a pilot campaign was performed in which we were able to clear 13 m 3 of burnable waste as conventional non-radioactive waste. Highlights: A methodology for the characterisation of burnable waste is presented. Four contaminating material types and 700 exposure scenarios were considered. Total gamma counting was used as the primary measurement methodology. Fingerprints and scaling factors were calculated. The majority of waste in a pilot study was suitable for clearance.